PENATALAKSANAAN FISIOTERAPI PADA OSTEOARTHRITISGENU BILATERAL DENGAN MODALITAS ULTRASOUND, TENS, DAN TERAPI LATIHAN DI RSUD CILILIN KABUPATEN BANDUNG BARAT - Intan Marthaulina; Mira Asih Anggraeni; Ika Rahman (Journal of Health Science and Physiotherapy, 2021)
Osteoarthritis is a degenerative health disorder where there is stiffness and inflammation in the joints which is characterized by damage to joint cartilage so that it can cause pain in the joints of the hands, neck, back, waist, and most often the knee joints. After doing therapy 6 times, the results of the assessment of increasing functional values ​​in both knees, namely right knee tenderness T1 = 60mm to T6 = 50mm, right knee motion pain T1 = 70mm to T6 = 60mm, and silent pain T1-T6 = 10mm, and the left knee showed tenderness T1=30mm to T6=10mm, motion pain T1=65mm to T6=60mm, and silent pain T1-T6=10mm. Increased muscle value in both legs, namely the right knee flexor muscle T1= 3 to T6=4, on the left knee T1=4 becomes T6=5, and the right knee extensor muscle T1=3 becomes T6=4, and the left knee T1= 30mm becomes T6=3, becomes T6=4. Ultrasound, Trancutaneous Electrical Nerve Stimulation (TENS) and Exercise Therapy can help reduce pain, improve basic functional and increase muscle strength in cases of Bilateral Genu Osteoarthritis